The effect of an alginate carrier on bone formation in a hydroxyapatite scaffold. Issue 7 (27th June 2015) - Coathup, Melanie J.; Edwards, Thomas C.; Samizadeh, Sorousheh; Lo, Wei‐Jen; Blunn, Gordon W.
Abstract: This study investigated the osteoconductive properties of a porous hydroxyapatite (HA) scaffold manufactured using a novel technique similar to the bread‐making process, alone and in combination with an alginate polysaccharide fiber gel (HA/APFG putty) and autologous bone marrow aspirate (BMA). The hypothesis was that the HA/APFG putty would be as osteoconductive as granular HA and that the presence of BMA would further enhance bone formation in an ovine femoral condyle critical defect model. Thirty‐six defects were created and either (1) porous HA granules, (2) HA/APFG putty, or (3) HA/APFG putty + BMA were implanted. After retrieval at 6 and 12 weeks, image analysis techniques were used to quantify bone apposition rates, new bone area, bone–HA scaffold contact, and implant resorption. At 6 weeks postsurgery, significantly lower bone apposition rates were observed in the HA/APFG putty group when compared to the HA ( p = 0.014) and HA/APFG putty + BMA ( p = 0.014) groups. At 12 weeks, significantly increased amounts of new bone formation were measured within the HA scaffold (33.56 ± 3.53%) when compared to both the HA/APFG putty (16.69 ± 2.7%; p = 0.043) and the defects containing HA/APFG putty + BMA (19.31 ± 3.8%; p = 0.043). The use of an APFG gel as a carrier for injectable CaP bone substitute materials delayed bone formation in this model compared to HA granules alone which enhanced bone formation especially within the interconnected smaller pores. Our results also showed that the addition of autologous BMA did not further enhance its osteoconductive properties. Further study is required to optimize the degradation rate of this APFG binding agent before using as a directly injectable material for repair of bone defect. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 104B: 1328–1335, 2016.